Impact of indigenous publishing on educational development in Nigeria: a case study of selected publishers in Ibadan (2018)
Four publishing companies in Ibadan were sampled to determine their impact on availability and accessibility of indigenous books in Nigeria educational sector, the impact of indigenous publishing on educational development in Nigeria, constraints to indigenous publishing in Nigeria and ways of promoting indigenous publishing in Nigeria. A survey of quantitative method was conducted with questionnaire as data gathering instrument. The population of study was 100 being the sum of 25 respondents randomly selected from each publishing company. Frequency counts and percentages were adopted for data analysis. Results showed that that indigenous books are available and accessible in Nigeria education sector, supplementary reading of indigenous books impacted much, poor sales promotion of indigenous materials’ has the most strong factor among all the factors highlighted as possible constrains to indigenous publishing in Nigeria, and that organizing reading campaigns among students will be the most possible way in promoting indigenous publishing in Nigeria. The study concluded that authors write on indigenous materials in Nigeria and these made Indigenous books are available and accessible in Nigeria education sector. It therefore among others recommends that there is a need to create conducive environment for indigenous publishers to compete with their contemporaries in other countries while government should gear all its effort towards revitalizing the moribund Nigeria paper mill.